TINDAK TUTUR DIREKTIF BERTANYA PADA PROSES PEMBELAJARAN BAHASA INDONESIA DI KELAS X - Rahmat Prayogi; Bambang Riadi; Rian Andri Prasetya (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2020)
This research is conducted to describe the form of directive speech acts and the politeness speech acts between the teacher and the students in Indonesian language learning process in class X. The research of the method is qualitative descriptive. The source of data is the form of directive speech act of teacher and students. The teqnique of the collection data is by using observasions in free technique and field notes. The analysis of the data is heuristic analysis tecnique. The results of the research showed that the form teacher of speech acts of asking for.  Those speech acts is delivered in directly and indirectly with the various modus. The politeness directive speech acts between the teacher and the students of the politeness linguistics and the pragmatics.